A replacement of plant protein sources as an alternative of fish meal ingredient for African catfish, Clarias gariepinus: A review - Zulhisyam, Abdul Kari; Muhammad Anamul, Kabir; Mohammad Khairul Azhar, Abdul Razab; Mohammad Bodrul, Munir; Po, Teen Lim; Lee, Seong Wei (UMK Publisher, 2020)
Aquaculture is one of the fastest growing industries in the world. This industry supplies half of the fisheries products consumed annually, and future global demand can only be supplied by increasing aquaculture production, which, in turn, requires more aquafeed. Alternative ingredients must be increasingly used to supply significant proportions of protein and energy in aquafeeds, creating both challenges and opportunities for researchers and industry. Nowadays, there are too many researches on fish disease, growth and health but less in a fish feed especially a replacement of protein from plant sources in the fish feed. One of the alternative ways to optimise the growth and health condition of the fish is provide them a good protein from plant as a replacement in fish meal with the natural source protein instead of giving a good rearing condition and caring of the fish. The present article was constructed to highlight a replacement of plant protein sources as an alternative of fish meal for fish feed in African catfish, Clarias gariepinus that has been done by researchers. However, the application of replacement from plant protein sources in fish meal is now gradually gaining importance in commercial aquaculture practices and opened the door for the researchers to expend of this application, thus more detailed studies on molecular basis should be looked as to get the quality and enough nutrient fish feed for good production of aquaculture industry.